The druid - Wheeler, Jeff, 1971- (Wheeler, Jeff, 1971- Dawning of Muirwood, 2022)
"Eilean was born a "wretched"--A lowly foundling raised by the Aldermaston of Tintern Abbey. Then she's chosen to assist in establishing the new abbey of Muirwood, now the site of a castle in the swampy Bearden Muir. Eilean's role is as night servant to the druid Mordaunt, the king's exiled advisor--and prisoner. He's clever, dangerous, and invaluable to the Aldermaston. Mordaunt's priceless secret: the hiding place of an ancient tome that reveals the existence of other worlds and the magic between them. Mordaunt knows how potent its words are and how dangerous they could be in the wrong hands. But can Eilean win him over? All she must do is gain Mordaunt's confidence and trust and persuade the apostate to divulge his secret to her. But as she learns more from Mordaunt, Eilean's loyalties begin to fray. And the risks are greater than she imagined. Despite betrayals, deceptions, and the deadly motivations of others, a girl from the flax fields is about to rise above her station. By exploring the potential of the power of an ancient spoken magic, Eilean is coming into her own."--